The Role of School Curriculum in Promoting Citizenship Values among Intermediate School Students In the Kingdom of Saudi Arabia from the point of view of teachers - Alghamdi, Mansour Ahmed; Al-Bdour, Ahmad Hasan (Journal of Curriculum and Teaching Methodology, 2022)
The research aimed to determine the role of school curriculum in promoting citizenship values among intermediate school students from the teachers’ point of view, and to reveal the differences between the means of teachers’ responses about the role of school curriculum in promoting citizenship values among intermediate school students according to the number of years of teaching experience and academic specialization. The descriptive approach was used by the survey method, and a questionnaire was applied to a sample size of (216) teachers, after verifying its stability, validity, and suitability for application, the research found that teachers agree with a high degree of appreciation on the role of school curriculum in promoting the values of citizenship among intermediate school students, and that the fields of citizenship values that school curriculum had a role in promoting among intermediate school students also came with a high degree of appreciation for all three fields (the security and civil field, the social and cultural field, and the political and economic field) which are ordered according to the arithmetic mean. The research also found that there are no statistically significant differences between the viewpoint of intermediate school teachers on the role of school curriculum in promoting the values of citizenship among intermediate school students according to the number of years of teaching experience, while there are statistically significant differences in the role of school curriculum in promoting the values of citizenship among intermediate school students. Intermediate school students from the teachers’ point of view according to the variable of academic specialization, and Post Hoc test did not appear in favor of any specialization. The research recommended a number of recommendations, which are summarized in the inclusion of lessons that reinforce the importance of citizenship values in the school curriculum for the intermediate stage.